2004
DOI: 10.1073/pnas.0405321101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rhizobium etli and of its symbiosis with wild Phaseolus vulgaris supports coevolution in centers of host diversification

Abstract: Common beans (Phaseolus vulgaris) comprise three major geographic genetic pools, one in Mexico, Central America, and Colombia, another in the southern Andes, and a third in Ecuador and northern Peru. Species Rhizobium etli is the predominant rhizobia found symbiotically associated with beans in the Americas. We have found polymorphism in the common nodulation gene nodC among R. etli strains from a wide range of geographical origins, which disclosed three nodC types. The different nodC alleles in American strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
2
43

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(190 citation statements)
references
References 32 publications
7
138
2
43
Order By: Relevance
“…Although few studies have reported on the genetic diversity of Rhizobium in Ecuador (Ribeiro et al, 2013), this is the first report of species diversity in the southern region of the country. Similar to this study, R. etli, R. leguminosarum and R. tropici have been previously isolated from common bean nodules (Martínez-Romero, 2003;Aguilar;Riva;Peltzer, 2004;Oliveira et al, 2011) and are considered to be the predominant occupant species of bean nodules in the Andean region (Junier et al, 2014;Ribeiro et al, 2015). Ecuador, north of Peru, Colombia and the Andean Region are currently considered to be the centers of domestication/diversity of the common bean (Oliveira et al, 2011).…”
Section: Resultssupporting
confidence: 75%
“…Although few studies have reported on the genetic diversity of Rhizobium in Ecuador (Ribeiro et al, 2013), this is the first report of species diversity in the southern region of the country. Similar to this study, R. etli, R. leguminosarum and R. tropici have been previously isolated from common bean nodules (Martínez-Romero, 2003;Aguilar;Riva;Peltzer, 2004;Oliveira et al, 2011) and are considered to be the predominant occupant species of bean nodules in the Andean region (Junier et al, 2014;Ribeiro et al, 2015). Ecuador, north of Peru, Colombia and the Andean Region are currently considered to be the centers of domestication/diversity of the common bean (Oliveira et al, 2011).…”
Section: Resultssupporting
confidence: 75%
“…These strains are representative lineages of the geographic regions corresponding to the two common bean domestication centers, Mesoamerican and Andean. According to our previous findings, common bean is preferentially and more efficiently nodulated by R. etli strains that coevolved in the same geographic region (Aguilar et al, 2004;Peltzer Meschini et al, 2008). Upon rhizobial inoculation, RabA2 mRNA levels increased in the entire root and to a higher extent in A phylogenetic tree of Arabidopsis Rab proteins and RHS24-03 (arrow) was generated using MEGA4 from a ClustalW alignment (available as Supplemental Data Set 1 online).…”
Section: Raba2 Is Expressed In Root Hairs and Nodulesmentioning
confidence: 72%
“…These strains were chosen as representatives of the main polymorphic forms of the nodC gene associated with domestication centers of common bean (Aguilar et al, 2004). Despite the fact that RabA2 was obtained in a screening as differentially expressed in root hairs treated with either of these strains, overexpression of RabA2 did not change the strain preference previously reported (Peltzer Meschini et al, 2008) or have any noticeable effect on nodulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is in agreement with the significant differences recorded between the genetic structure and the diversity of the bacterial communities associated with the two uncultivated soils (data not shown). This hypothesis of coevolution in centers of host diversification between plants and associated soil-borne microorganisms has recently been proposed when analyzing Rhizobium etli diversity and its symbiosis with Phaseolus vulgaris (1). Besides their origins, the two soils also differ in their levels of fertility.…”
Section: Discussionmentioning
confidence: 95%